1975 International Electron Devices Meeting 1975
DOI: 10.1109/iedm.1975.188884
|View full text |Cite
|
Sign up to set email alerts
|

An n-channel Si-gate integrated circuit technology

Abstract: A high speed, LSI, n-channel Si-Gate technology has been developed and characterized for the manufacture of integrated circuits. Utilizing the advantages of local oxidation and ion implantation, a technology is achieved which is: (a) fabricated on high resistivity Si substrates; (b) quasi-planar in topological structure; (c) completely adjustable in gate threshold voltage (enhancement and depletion modes) and field threshold voltage; and (d) highly reproducible in electrical parameter control. Additionally, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some detailed profiles obtained from "hi-lo" VPE n-GaAs (modified Read IMPATT material) are also presented. Emphasis is placed on the very high levels of reproducibility required from the profiling technique in this area of application (4,5).…”
Section: Applications Of Electrochemical Methods Formentioning
confidence: 99%
See 2 more Smart Citations
“…Some detailed profiles obtained from "hi-lo" VPE n-GaAs (modified Read IMPATT material) are also presented. Emphasis is placed on the very high levels of reproducibility required from the profiling technique in this area of application (4,5).…”
Section: Applications Of Electrochemical Methods Formentioning
confidence: 99%
“…It has been observed that this processing scheme produces a bird's beak configuration (1)(2)(3)(4) at the edge of the isolation oxide, and that subsequent gate oxidation (after removal of masking Si3N4) often results in a thinning of the gate oxide next to the isolation oxide. The thinning of the gate oxide has been attributed to the presence of a thin layer of a Si nitride (or oxynitride) on the Si which serves as a barrier to oxida-tion; the nitride is believed to occur as a result of N I ~ generation f r o m the masking Si3N4 during isolation oxidation followed by interaction of the NHa w i t h the Si substrate (2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The polysilicon regions may serve as an FET gate, a capacitor plate, an interconnection line, or a contact area. Then an insulation oxide is thermally grown and/or deposited over the structure [10]. The third masking pattern defines contact vias to source, drain, and polysilicon areas.…”
Section: Self-registering Contact Techniquementioning
confidence: 99%